W IMIĘ WSPÓLNYCH WARTOŚCI. ŚWIĘTEJ PAMIĘCI PREZYDENTA LECHA KACZYŃSKIEGO (1949-2010) - Zabłocki, Jan (Zeszyty Prawnicze, 2016)
W IMIĘ WSPÓLNYCH WARTOŚCI. ŚWIĘTEJ PAMIĘCI PREZYDENTA LECHA KACZYŃSKIEGO (1949-2010)